Norme, écart et usages : premiers éléments d’une étude sur les anciens collèges jésuites en Auvergne-Rhône-Alpes - Catherine Guégan (In Situ)
This article aims to establish an inventory of a current study of seventeen Jesuit colleges, located in a territory that intersects the former Jesuit provinces of Lyon, Toulouse and France. The chronological framework chosen runs from the creation of the first Jesuit college in France, in 1556, to the date of expulsion of the order from the kingdom of France, in 1762.On the one hand, we intend to compare the general framework of the regulations established by the Society of Jesus for the construction of its houses, particularly attentive to the questions of functionality and adaptation of spaces to liturgical, community and educational needs, and the design and implementation arrangements for the construction of the studied colleges, and on the other hand, to show how these rules could be reconciled with local constraints and uses, reflecting the flexibility and adaptability of the Society’s members to the specifics of each territory.The questions asked by this contribution are the following: can we highlight a network of Jesuit colleges (points and degrees of similarity in design and construction, filiations and variants, singularities, etc.) as ancestors/models for high schools from 1802 onwards, especially in terms of their location and distribution? And can we define precisely the role that the members of the Society played in the construction and organisation of this network and the dissemination of models?